Pemberian Mikoriza Dalam Media Tanam Campuran Limbah Kelapa Sawit Terhadap Pertumbuhan Bawang Merah (Allium ascalonicum) - Dedi Kurniawan; Siti Khairani (Universitas Teuku Umar, 2023)
The objectives of this research were to determine the effect of mycorrhizae, media mixture palm oil waste, interaction between mycorrhizae and media mixture palm oil waste. This research used a Randomized Block Design consisting of two factors, which were concentration of mycorrhizae (0, 50, and 100 g/plant) and level of media mixture palm oil waste (top soil, top soil + TKKS (1:1), top soil + fiber (1:1), and top soil + sludge (1:1)). Results showed that the treatment of mychorrizae and mixed media give significant effect on number of leave, fresh dan dry tuber weight for plant. The giving mycorrhizae 50 g/plant increased number of leave (21,85 sheet), fresh tuber weight (27,48 g), and dry tuber weight (21,21 g). Media of top soil + sludge increased number of leave (23,60 sheet), fresh tuber weight (32,35 g), and dry tuber weight (24,16 g). The addition of mycorrhizae and media mixture palm oil waste can increase results of onion.